2002
DOI: 10.1021/jm0104217
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Hypoxic Selectivity in Copper Bis(Thiosemicarbazone) Radiopharmaceuticals

Abstract: Copper diacetyl-bis(N4-methylthiosemicarbazone), Cu(II)ATSM, is a promising agent for imaging hypoxic tissue. Here we present results that provide insight into the chemical and electronic properties underlying previously observed structure-activity relationships. Density functional theory (DFT) calculations on the electronic structures and molecular orbitals of a series of 13 Cu(II)bis(thiosemicarbazone) analogues with different alkylation patterns and with fixed geometries based on the known structure of Cu(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 40 publications
5
165
0
1
Order By: Relevance
“…Importantly, once Cu II (gtsm) is exposed to the intracellular reducing environment, Cu II is reduced to Cu I , causing it to dissociate from the ligand and to increase Cu bioavailability. The negative control Cu II (atsm) does not reduce and dissociate under normal intracellular conditions, and therefore does not increase Cu bioavailability (18,(23)(24)(25)(26). We found both metal complexes increased cellular Cu levels several hundredfold ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Importantly, once Cu II (gtsm) is exposed to the intracellular reducing environment, Cu II is reduced to Cu I , causing it to dissociate from the ligand and to increase Cu bioavailability. The negative control Cu II (atsm) does not reduce and dissociate under normal intracellular conditions, and therefore does not increase Cu bioavailability (18,(23)(24)(25)(26). We found both metal complexes increased cellular Cu levels several hundredfold ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…If the lifetime of the stable complex inside the cell is thought of as a cycling between reduction and oxidation, re-oxidation of the unstable complex from Cu(I) to Cu(II) by molecular oxygen is likely to be a key regulator of whether these tracers dissociate and deposit their radiocopper, or diffuse back out of the cell unchanged. This has been shown to be possible chemically in a non-biological system, but as yet, this has not been demonstrated in live cells [115]. The relative importance of these two mechanisms is currently unknown.…”
Section: What Is the Role Of Oxygen?mentioning
confidence: 97%
“…One further potential modifier of BTSC complex dissociation is protonation, which may be more prevalent during acidosis [96,115,116]. While it has been shown in vitro that Cu-BTSC complexes are stable under acidic but oxygenated conditions [113,115], and at this time there is no experimental data to directly support cellular retention of radiocopper by protonation alone, density functional theory calculations by Holland et al suggest that a decrease in cellular pH may protonate the unstable Cu(I) complex, and increase its rate of dissociation [116,117].…”
Section: What Is the Effect Of Acidosis?mentioning
confidence: 99%
See 1 more Smart Citation
“…14 In another study, the bis(thiosemicarbazone) complexes of copper have shown special promise as radiopharmaceuticals, as illustrated by a per fusion imaging agent. [15][16][17][18][19] In the recent studies, appear to be a structural class with anti-pox virus activity. 20 Isatin derivatives such as methisazone (marboran), the β-thiosemicarbazone of N-methyl isatin, have been described as smallpox chemoprophylactic agents.…”
Section: Introductionmentioning
confidence: 99%